Germline variants of uncertain significance, their frequency, and clinico-pathological features in a cohort of Sri Lankan patients with hereditary breast cancer - Kawmadi Gunawardena; Nirmala D. Sirisena; Gayani Anandagoda; Nilaksha Neththikumara; Vajira H.W. Dissanayake (BMC Research Notes, 2023)
Abstract Background Next-Generation Sequencing (NGS)-based testing in cancer patients has led to increased detection of variants of uncertain significance (VUS). VUS are genetic variants whose impact on protein function is unknown. VUS pose a challenge to clinicians and patients due to uncertainty regarding their cancer predisposition risk. Paucity of data exists on the pattern of VUS in under-represented populations. This study describes the frequency of germline VUS and clinico-pathological features in Sri Lankan hereditary breast cancer patients. Methods Data of 72 hereditary breast cancer patients who underwent NGS-based testing between January 2015 and December 2021 were maintained prospectively in a database and analyzed retrospectively. Data were subjected to bioinformatics analysis and variants were classified according to international guidelines. Results Germline variants were detected in 33/72(45.8%) patients, comprising 16(48.5%) pathogenic/likely pathogenic variants and 17(51.5%) VUS. Distribution of VUS in breast cancer predisposing genes were :APC:1(5.8%), ATM:2(11.7%), BRCA 1:1(5.8%), BRCA 2:5(29.4%), BRIP 1:1(5.8%), CDKN 2A:1(5.8%), CHEK 2:2(11.7%), FANC 1:1(5.8%), MET:1(5.8%), STK 11:1(5.8%), NF 2:1(5.8%). Mean age at cancer diagnosis in patients with VUS was 51.2 years. Most common tumour histopathology was ductal carcinoma 11(78.6%). 50% of tumours in patients having VUS in BRCA 1/2 genes were hormone receptor negative. 73.3% patients had family history of breast cancer. Conclusions A significant portion of patients had a germline VUS. Highest frequency was in BRCA 2 gene. Majority had family history of breast cancer. This highlights the need to undertake functional genomic studies to determine the biological effects of VUS and identify potentially clinically actionable variants that would be useful for decision-making and patient management.